(untitled) (Journal of Agriculture and Natural Resources, 2021)
This study explores the relationship between climate variables to rice production in Kaski and Nawalparasi district of Nepal. The study was conducted in the year 2016. This study captured the time series data ranging from 1995 to 2014 on rice production, temperature and rainfall of two different districts and analyzed through panel data regression. Regarding primary data collection, a total of 120 sampled households were surveyed by using simple random sampling to understand the perception of farmers to change in climatic parameters using a semi-structured pre-tested questionnaire and Focus Group Discussions. The secondary information was collected from the Ministry of Agriculture and Livestock Development, Department of Hydrology and Meteorology and Centre Bureau of Statistics. The regression model revealed that seasonal rainfall had a linear relation on rice production (p<0.05). Respondents from both districts perceived that temperature, rainfall and hailstone had increased or varied than before. The major problems faced by the farmers of the study area due to climate change were prioritized as drought, flood hailstone, extreme hot and extreme cold. This necessitates the promotion and use of climate-smart technologies for better rice adaptation to climate change.